Pengaruh Motivasi dan Perilaku Belajar Terhadap Indeks Prestasi Mahasiswa Pendidikan Agama Islam Universitas Islam Negeri Salatiga - Mahardhika, Aditya Putra; Rosyida, Chusna Nur; Purnomo, Purnomo (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
The goals of this study are to ascertain (1) whether there is an effect of learning motivation and learning behavior, partially or simultaneously, on students’ GPA. The study's methodology is quantitative and correlational in nature. The population of this study was 117 IRE students from the 2022 batch of Universitas Islam Negeri Salatiga, and a sample of 60 students was selected using a stratified sampling method. According to the study's findings, there is no correlation between learning motivation and students’ GPA (significantly 0,719), no correlation between learning behavior and students’ GPA (significantly 0,382), and no correlation between motivation and learning behavior simultaneously with students’ GPA (significantly 0,579). The variables of motivation and learning behavior can only explain 1.9% of the students’ GPA, while the remaining 98.1% is influenced by other factors not examined. Therefore, in conclusion, motivation and learning behavior do not significantly influence student achievement index, either partially or simultaneously.